2007
DOI: 10.1007/s10600-007-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

Shawurensine, a new C19-diterpenoid alkaloid from Delphinium shawurense

Abstract: The new norditerpenoid alkaloid shawurensine in addition to β-sitosterol and the known alkaloids elatin, delbrulin, and methyllycaconitine were isolated from Delphinium shawurense. A structure for shawurensine was proposed based on spectral data.Plants of the genus Delphinium (Ranunculaceae) are sources of diterpenoid alkaloids. Therefore, many species of this genus are used in folk medicine [1]. However, data on the chemical composition and use of D. shawurense W. T. Wang in folk medicine have not been publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, eleven known diterpenoid alkaloids were determined to be delbruline ( 5 ) [ 11 ], delpheline ( 6 ) [ 13 ], lycoctonine ( 7 ) [ 11 ], delbrunine ( 8 ) [ 11 ], delcosine ( 9 ) [ 11 ], uraphine ( 10 ) [ 14 ], anthranoyllycoctonine ( 11 ) [ 15 ], sharwuphinine A ( 12 ) [ 16 ], browniine ( 13 ) [ 11 ], shawurensine ( 14 ) [ 17 ], and delavaine B ( 15 ) [ 17 ] by comparison of their corresponding spectroscopic data with those reported previously in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, eleven known diterpenoid alkaloids were determined to be delbruline ( 5 ) [ 11 ], delpheline ( 6 ) [ 13 ], lycoctonine ( 7 ) [ 11 ], delbrunine ( 8 ) [ 11 ], delcosine ( 9 ) [ 11 ], uraphine ( 10 ) [ 14 ], anthranoyllycoctonine ( 11 ) [ 15 ], sharwuphinine A ( 12 ) [ 16 ], browniine ( 13 ) [ 11 ], shawurensine ( 14 ) [ 17 ], and delavaine B ( 15 ) [ 17 ] by comparison of their corresponding spectroscopic data with those reported previously in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Ten known compounds, methyllycaconitine ( 6 ), shawurensine ( 7 ), delavaine A ( 8 ), delavaine B ( 9 ), delsemine A ( 10 ), delsemine B ( 11 ), tianshanisine ( 12 ), delcorine ( 13 ), 6‐deoxydelpheline ( 14 ) and blacknidine ( 15 ), were identified by comparison of their spectroscopic data with the literature data.…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical studies have revealed that D. aemulans contains 15 compounds including 11 diterpenoid alkaloids, aemulanitine, deacetylaconorine, 14-acetylaconorine, cammaconine, aconorine, napelline, 1-acetylluciculine, 12acetylnapelline, dehydronapeline, songorine and songoramine [6]. During our further investigation for more bioactive compounds on the whole herb of D. aemulans, one new C 19 -diterpenoid alkaloid aemulansine (1), together with ten known C 19 -diterpenoid alkaloids, delsoline (2) [7], delavaine A (3), delavanie B (4) [8], methyllycaconitine (5) [9], delcosine (6) [10], shawurensine (7) [11], lycoctonine (8) [12], anthranoyllycoctonine (9) [13], delphatine (10) [14] and ajadine (11) [15] were isolated and their structures ( Figure 1) were elucidated by means of spectroscopic analyses and comparison with data reported in the literature. In this paper, the isolation, structural elucidation and cytotoxicity of these compounds are described.…”
Section: Delphinium Aemulansmentioning
confidence: 99%